The Use of Virtual Reality as A Substitute for The Pre-School Students’ Field Trip Activity During the Learning from Home Period - Farah Firdiarahma (Universitas Pendidikan Indonesia (UPI), 2021)
This study aims to examine the use of virtual reality as a substitute for the pre-school students' field trip activity during the learning from the home period. This research used a literature study as the research methodology. We conducted this study by observing and analyzing several journals on the use of Virtual Reality as a medium of learning. The various results of the journal analysis were used to determine whether virtual reality could be a substitute for the pre-school students’ field trip learning activity in this learning from the home period. By using Virtual Reality, the students would still be able to participate in field trips while still pays attention to the steps of conducting a field trip, such as (1) planning and preparation period; (2) the execution of the event, and; (3) the return time. Besides being considered as an effective tool to increase students’ learning interest and improve their learning outcomes, virtual reality can also be a substitute for the real field trips during this Covid-19 pandemic. Therefore, the students do not need to leave the house to participate in field trips. Hopefully, the result of this research would be able to provide the readers with new insights and knowledge on the utilization of virtual reality as a substitute for the pre-school students’ real field trip activity especially in this learning from the home period.